Konsep Kepribadian Sigmund Freud Dan Relevansi Dengan Pendidikan Islam Anak Usia Dini - Pasiska; Manora, Hecksa; Nurlila Kamsi (Bouseik: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Personality development in early childhood is a crucial phase that greatly influences the formation of individual character and behavior in the future. One of the theories that provides deep insight into this dynamic is Sigmund Freud's psychoanalytic theory, which divides the structure of human personality into three main elements: id, ego, and superego. However, in the context of Islamic education, personality formation is not only limited to psychological aspects, but also includes the cultivation of spiritual values, creed, and morals derived from religious teachings. This study aims to analyze the relevance of Sigmund Freud's personality concept in the framework of early childhood Islamic education, especially in an effort to understand children's internal conflicts and direct their development to be in harmony with Islamic values. The research method used is qualitative descriptive with a library research approach. Data was collected through a review of a variety of relevant literature, including books and scientific journal articles from online databases such as Google Scholar and DOAJ. Data analysis techniques are carried out systematically through content analysis, which includes the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the integration between Freud's psychoanalytic approach and Islamic educational principles can produce a holistic educational strategy for early childhood. Through understanding the dynamics of the subconscious, educators can help children recognize their internal conflicts and impulses, which are then directed to form mature moral habits in accordance with religious guidance. The merging of these two perspectives makes an important contribution to education practitioners and parents in optimizing a balanced parenting process between aspects of psychological development and children's spiritual maturity.